The perceived usefulness of financial information for decision making in Portuguese municipalities the importance of internal control - Nogueira, Sónia P. (2018)
The purpose of this paper is to analyse the extent to which the perceived usefulness of financial information for internal decision making is affected by the internal control to which that information is subjected. Design/methodology/approach: The research is positivist and quantitative, based on a cross-sectional analysis developed in the local government context. Data were collected from a survey to decision makers (politicians and chief officials) in charge of the financial area in all Portuguese municipalities. The response rate was approximately 49 per cent, assuring representativeness. Findings: Regarding the perceived usefulness of financial and budgetary reporting for internal decision making, the results in the paper show that municipalities' internal users' attitudes towards using accrual-based financial reporting for decision making is changing. Additionally, internal decision makers consider financial and budgetary information as very useful for decision making, and the different types of internal control applicable to that information as very important. The results also clearly point to the existence of a significant and positive relationship between the internal control (including internal auditing) to which financial and budgetary information is subject, and its perceived usefulness for municipal decision making. Research limitations/implications: The main limitations of this study are related to the way in which information was collected in order to obtain empirical evidence. The questionnaire, sent by e-mail, despite reaching a wide-range and dispersed population, cannot guarantee the truthfulness and integrity of the responses. Findings might have been affected by the fact that respondents may have been sympathetic to the reforms brought by the Official Local Government Accounting Plan (POCAL). Certainly, politicians linked to the political party that promoted those reforms would be predisposed in this way. Another limitation might concern the fact that new laws and regulations passed after POCAL, might have somehow affected the answers regarding the perceived usefulness of budgetary and financial information for internal decision making, as well as the importance of the internal control to which that information is subject. Practical implications: The results of this study have important repercussions for the implementation of internal control systems at local government level. Particularly, they highlight the need to develop or improve internal control procedures to ensure budgetary and financial information reliability, which in turn determines its usefulness for decision-making purposes. Originality/value: This research makes a contribution to the (scarce) literature on the relationship between internal control and the perceived usefulness of financial and budgetary information for decision making, particularly in the local government setting. It adds with further empirical evidence concerning the relationship between these two issues, helping to reinforce previous embryonic research in this field. As to policy making, this research also contributes by calling attention for the need to define the types of internal control financial information must be subject, a critical issue while assuring the usefulness of that information for decision making. This is particular important in current contexts of countries moving towards IPSAS-based financial reporting systems.